The climate change regulatory framework and indigenous peoples’ lands in Africa: Human rights implications - Ademola Oluborode Jegede (Pretoria University Law Press (PULP), 2016)
Employing a human rights approach, this book analyses the adequacy of climate change regulatory frameworks at international, regional and national levels to protect indigenous peoples’ lands in Africa. It demonstrates that without appropriate legal protection, climate change and the implementation of its response measures can adversely affect a range of their human rights. The book explores how the African human rights system may effectively address the protection of indigenous peoples' lands in the context of adverse effects of climate change in Africa. Table of Contents Foreword Acknowledgments Dedication List of abbreviations Table of cases List of instruments 1. Introduction Background 1.1 Intersecting terms? Indigenous peoples, forest-dependent peoples and local populations 1.2 Overlapping issues? Climate change, environment, forests and indigenous peoples’ lands 1.3 Intersecting governance: Defining a climate change regulatory framework Methodology 2.1 A human rights framework as a tool of analysis 2.2 A human rights framework as a prescriptive tool 2.3 Case studies for analysis Limitations Synopsis 2. Human rights and climate change: Conceptual framework Introduction Climate change: An environmental or human rights concern? 2.1 Climate change as an environmental concern 2.2. Climate change as a human rights concern Human rights as a conceptual framework: Which approach and what features? 3.1 Human rights and schools of thought 3.2 Core human rights principles Conclusion 3. The notion of indigenous peoples’ land rights and adverse effects of climate change in Africa Introduction The nature of indigenous peoples’ land rights 2.1 Land use as an emblem of cultural and environmental integrity 2.2 Indigenous peoples’ land tenure: Essential features 2.3 Concept of parallel use Cause and effect of climate change as threat to land-tenure and use 3.1 Cause of climate change as a threat 3.2 Climate change as a threat 3.3 Effects of climate response as a threat Conclusion 4. The international climate change regulatory framework in relation to indigenous peoples’ lands Introduction Regulatory frameworks on the responses to climate change 2.1 The international adaptation regulatory framework 2.2 The international regulatory framework and mitigation Subordinating notions in the international climate regulatory framework 3.1 Notion of ‘sovereignty’ 3.2 Notion of ‘country-driven’ 3.3 Deference to ‘national legislation’ Conclusion 5. National climate change regulatory frameworks in relation to indigenous peoples’ lands: Case studies of Tanzania, Zambia and Nigeria Introduction Significance of a domestic regulatory framework Domestic climate change regulatory response of adaptation 3.1 Implications of inadequate reflection of land tenure and use in adaptation process National climate change regulatory response of REDD+ as a mitigation measure 4.1 REDD+ readiness in selected states of Africa in relation to indigenous peoples’ lands Conclusion 6. The inadequacy of the national climate change regulatory framework in relation to indigenous peoples’ lands: A human rights framework as a regional response Introduction Legal basis for the application of a regional human rights framework Assessing national regulatory frameworks in the context of a regional human rights framework 3.1 Incompatibility of national climate regulatory framework with obligations of states 3.2 Threat to a range of rights The regional climate change regulatory framework and potential for human rights 4.1 Committee of African Heads of State and Government on Climate Change 4.2 African Ministerial Conference on the Environment 4.3 Climate for Development in Africa (ClimDev-Africa) Programme 4.4 African Union Commission 4.5 New Partnership for African Development 4.6 Pan-African Parliament 4.7 Peace and Security Council Potentials in regional human rights mechanisms with focus on the Commission 5.1 Promotional functions 5.2 Protective mandate 5.3 Interpretive functions 5.4 Assembly-entrusted tasks Conclusion 7. Conclusion and the way forward Conclusion The way forward 2.1 International level 2.2 National level 2.3 Regional level Bibliography Index